Motivation as a Predictor of Aphasia Treatment Outcomes: A Scoping Review. Issue 3 (July 2022) - Weatherill, Maryanne; Tibus, Elizabeth O.; Rodriguez, Amy D.
Abstract : Purpose: Motivation is a complex phenomenon that can influence a person's ability to make progress in treatment. We sought to understand how motivation is currently measured and utilized in aphasia rehabilitation by identifying treatment studies that (1) include measurement of motivation and (2) use motivation to predict treatment response. Method: A scoping review was conducted by systematically searching PubMed, CINAHL, EBSCO, Ovid MEDLINE, and APA PsycInfo using the following search terms: (measurement OR treatment OR rehabilitation OR predict*) AND (motiv* OR engagement OR adherence OR compliance) AND (aphasia OR dysphasia). Results: Two studies met our inclusion criteria. Motivation was measured differently across studies. No studies used motivation to predict treatment outcomes. Discussion/Conclusions: Despite the importance of motivation in aphasia rehabilitation success, studies that include its measurement are sparse. Additional research is needed and should include development of measurement tools and evaluation of the predictive value of motivation on treatment outcomes.